2018
DOI: 10.1128/aac.00401-18
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of E1224-Benznidazole Combination Treatment for Infection with a Multidrug-Resistant Trypanosoma cruzi Strain in Mice

Abstract: Combination therapy has been proposed as an alternative therapeutic approach for the treatment of Chagas disease. In this study, we evaluated the effect of treatment with benznidazole combined with E1224 (ravuconazole prodrug) in an experimental murine model of acute infection. The first set of experiments assessed the range of E1224 doses required to induce parasitological cure using Trypanosoma cruzi strains with different susceptibilities to benznidazole (Y and Colombian). All E1224 doses were effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…When a rigorous evaluation of the curative efficacy of drugs used alone or in combination was performed 30 days posttreatment by immunosuppression of treated animals and monitoring the reactivation of Y strain infections with a blood quantitative PCR (qPCR), it was confirmed that the use of allopurinol/benznidazole in combination prevented death and eradicated the parasitic infection with an efficacy (100% cure) superior to that of the reference treatment (70% cure with 100 mg/kg of benznidazole). As the efficacy of the treatment of mouse infection has been related to the parasite strain and the time of infection (39, 40), studies designed to treat mice infected with parasites belonging to other T. cruzi discrete typing units, as well as chronically infected animals, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…When a rigorous evaluation of the curative efficacy of drugs used alone or in combination was performed 30 days posttreatment by immunosuppression of treated animals and monitoring the reactivation of Y strain infections with a blood quantitative PCR (qPCR), it was confirmed that the use of allopurinol/benznidazole in combination prevented death and eradicated the parasitic infection with an efficacy (100% cure) superior to that of the reference treatment (70% cure with 100 mg/kg of benznidazole). As the efficacy of the treatment of mouse infection has been related to the parasite strain and the time of infection (39, 40), studies designed to treat mice infected with parasites belonging to other T. cruzi discrete typing units, as well as chronically infected animals, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…After confirmation of infection, animals in the SIT and TIT groups received daily treatment with Bz (100 mg kg −1 , administered by gavage) for 30 days (LAFEPE, Pernambuco, Brazil). The Bz dose was based on the reference dose used in preclinical models of Chagas disease supported by the Drugs for Neglected Disease initiative (DNDi, Geneva, Switzerland) (Diniz et al ., 2018). Fourth-eight hours after the last treatment, the animals were anesthetized (150 mg kg −1 ketamine and 16 mg kg −1 xylazine) and euthanized by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%
“…Cure was detected in mice infected by Y strain, but no cure was observed in Colombian infection in mice. [ 116 , 117 ] [ 118 ] VFV VFV was more potent than VNI in reducing parasitemia and presented effects on mortality protection. [ 60 , 119 ] VNI VNI presented promising anti- T. cruzi activity in vitro and in vivo.…”
Section: New Drug Candidates For Chagas Diseasementioning
confidence: 99%
“… [ 116 , 117 ] Fosravuconazole (E1224) prodrug of ravuconazole Antifungal E1224 was well tolerated and effective in suppressing parasitemia with cure in Y strain-infected mice. [ 118 ] Tipifarnib Anticancer Tipifarnib showed potent in vitro activity due to CYP51 T. cruzi inhibition. Tipifarnib analog had potent suppressive activity on parasitemia in infected mice.…”
Section: Drug Repurposingmentioning
confidence: 99%